Coral Reef: A Close-Up Look at the Natural World of a Coral Reef - Taylor, Barbara 1954- (New York : Dorling Kindersley, 1992)
Examines the variety of life found on coral reefs, including the seahorse, hermit crab, and sea slug.
Includes index.
Keywords: Coral reef fauna -- Juvenile literature